Health and safety procedures and their role in enhancing the reputation of higher education institutions A survey study of the opinions of a sample of students in the dormitories at the College of Administration and Economics at the University of Sulaiman - Sulaf Ezaldin Saeed al-Dalwi (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The current research sought to show the role of health and safety procedures on enhancing the organizational reputation of the University of Sulaymaniyah in the Kurdistan Region of Iraq, And that is from the point of view of a sample of students of the College of Administration and Economy residing in the student dormitories as individuals belonging to the university and they have an awareness of the procedures that university pursues in order to preserve their health and safety while they are inside the campus and students’ dormitories on the one hand,and its reflection on the university’s reputation from their point of view and their vision of it as being beneficiaries from the university who get various services such as education, housing, etc. from the other side.To achieve this, the researcher prepared a hypothetical scheme that includes research variables, in addition to formulating several main hypotheses that derive from it, The questionnaire was used for this purpose as a main tool for data collection, As (311) forms were distributed to a sample of (897) students from students’ dormitories of the researched college, (286) copies of a valid copy of the statistical analysis were received which were answered by them. A number of appropriate statistical methods were used to test the hypotheses of the research. Accordingly, the research reached a set of conclusions, the most important of which are: The health and safety procedures followed by the University of Sulaymaniyah at students’ dormitories have a great role in enhancing the university’s reputation by describing and analyzing the answers of the members of the research sample about both variables, Depending on this, the researcher presented a set of suggestions compatible with those conclusions.